Detection of microplastics and phthalic acid esters in sea urchins from Sardinia (Western Mediterranean Sea). (December 2022) - Raguso, Clarissa; Grech, Daniele; Becchi, Alessandro; Ubaldi, Paolo Giuseppe; Lasagni, Marina; Guala, Ivan; Saliu, Francesco
Abstract: The occurrence of microplastics (MPs) and phthalic acid esters (PAEs) in wild purple sea urchins ( Paracentrotus lividus ) of Sardinia (Italy, Western Mediterranean Sea) was surveyed. Specifically, MPs were analyzed in the digestive tract by μFTIR and PAEs in the gonads by SPME-LC-MS/MS. 9 out of 22 specimens resulted contaminated with MPs and 20 displayed levels of PAEs over the quantification limit. A total of 23 MPs were detected with a maximum concentration of 4 microplastics/individual in the commercially undersized specimens. PAEs displayed average concentration of 32 ng/g, σ = 5.3 with maximum value of 77 ng/g. The most abundant congeners were DEHP (17 ng/g, σ = 4.3) and DBP (10 ng/g, σ = 2.5). Statistical analysis showed correlation between DEHP and fiber concentrations and among the concentration of MEP, DEP, DBP and BBzP. Due to local use of sea urchin gonads as gourmet delicacy, the potential human exposition to MPs and PAEs by consumption is also discussed. Graphical abstract: Unlabelled Image Highlights: MPs and PAEs were researched in 22 wild sea urchins from Sardinia (Italy). A total of 23 MPs was detected with a maximum concentration of 4 MPs/individuals. ∑5 PAEs displayed average concentration of 32 ng/g, maximum of 77 ng/g. The human exposition to MPs and PAEs by sea urchin consumption was discussed.